Momentum-dependent quasiparticle properties of the Fermi polaron from the functional renormalization group - Milczewski, Jonas von; Schmidt, Richard (Physical review, 2024)
We study theoretically the lifetimes of attractive and repulsive Fermi polarons, as well as the molecule at finite momentum in three dimensions. To this end, we develop a technique that allows for the computation of Green's functions in the whole complex frequency plane using exact analytical continuation within the functional renormalization group. The improved numerical stability and reduced computational cost of this method yield access to previously inaccessible momentum-dependent quasiparticle properties of low-lying excited states. While conventional approaches like the non-self-consistent 𝑇-matrix approximation method cannot determine these lifetimes, we are able to find the momentum-dependent lifetime at different interaction strengths of both the attractive and repulsive polaron as well as the molecule. At weak coupling our results confirm predictions made from effective Fermi liquid theory regarding the decay of the attractive polaron, and we demonstrate that Fermi liquidlike behavior extends far into the strong-coupling regime where the attractive polaron and molecule exhibit a 𝑝4 momentum scaling in their decay widths. Our results offer an intriguing insight into the momentum-dependent quasiparticle properties of the Fermi polaron problem, which can be measured using techniques such as Raman transfer and Ramsey interferometry.